2016
DOI: 10.1590/1809-98232016019.150086
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of functional incapacity by gender in elderly people in Brazil: a systematic review with meta-analysis

Abstract: Considering that functional capacity is an important indicator of health in aging, the present study aimed to describe the prevalence of disability by gender among elderly people in Brazil through a systematic review and meta-analysis of articles about this subject. Articles published up to June 2013 were included, and a search was performed of the MEDLINE, SciELO, LILACS, Scopus, Web of Science and Science Direct electronic databases. The inclusion of articles in the systematic review was guided by the Streng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 41 publications
(50 reference statements)
2
15
0
8
Order By: Relevance
“…This result corroborates previous research performed in Brazil (16) in which older adults (≥65 years) with higher socioeconomic levels showed greater adherence to physical exercise regarding older adults of the same age and lower socioeconomic levels. Among the older adult population, clinical (comorbidities, functional disability, and depression) (17) and socio-demographic factors (lower levels of education and monthly income) are associated with poor adherence to physical exercise (18) . It is noteworthy that hydrogymnastic practice requires a monthly cost, and consequently, there is a higher demand among individuals with higher monthly incomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This result corroborates previous research performed in Brazil (16) in which older adults (≥65 years) with higher socioeconomic levels showed greater adherence to physical exercise regarding older adults of the same age and lower socioeconomic levels. Among the older adult population, clinical (comorbidities, functional disability, and depression) (17) and socio-demographic factors (lower levels of education and monthly income) are associated with poor adherence to physical exercise (18) . It is noteworthy that hydrogymnastic practice requires a monthly cost, and consequently, there is a higher demand among individuals with higher monthly incomes.…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that hydrogymnastic practice requires a monthly cost, and consequently, there is a higher demand among individuals with higher monthly incomes. However, there is no consensus on it, and some studies (17)(18)(19) show an inverse association between socioeconomic status and physical exercise practice in the older adult population.…”
Section: Discussionmentioning
confidence: 99%
“…20 Os fatores que impulsionam o envelhecimento populacional são distintos de outras experiências, em parte, pela heterogeneidade econômica, social, cultural e ambiental. 21,22 Junto com o envelhecimento, nota-se o aumento sempenho cognitivo, como a redução da atenção e da velocidade do processamento de informação. 37 As mudanças psicológicas com o envelhecimento resultam da dificuldade de adaptações a novos papéis sociais, falta de motivação, baixa-estima, dificuldade de mudanças rápidas, perdas afetivas e orgânicas, somatização, hipocondria e depressão.…”
Section: O Processo De Envelhecimentounclassified
“…Studies in Brazilian populations showed that women had a higher prevalence of functional incapacity when compared to men 2 , and there is an increase in the level of functional incapacity or limitation with age 3 . The anticipation to incapacitating processes is an important public health concern.…”
Section: Introductionmentioning
confidence: 98%
“…Ageing is characterized as a continuous, progressive, natural, and irreversible process that results in damage and alteration of morphological, functional, biochemical, and psychological systems and consequently reduces the functional reserves of organs and systems 1 . These modifications, associated to inadequate health behaviors, are factors that could increase the risk of incapacitating processes for the elderly 2 .…”
Section: Introductionmentioning
confidence: 99%